5. Isolation and Identification of Salmonella sp in spleen of male layer chicken in Sibreh farms, Aceh Besar - Erina Erina; Mahdi Abrar; Balqis Alrasyid Suyoto; Maryulia Dewi; Darmawi Darmawi; Darniati Darniati; Muttaqien Bakri (Universitas Syiah Kuala, 2017)
This study aimed to isolate and identify the bacteria Salmonella sp in spleen of male layer chicken that died in farms Sibreh, Aceh Besar. A sample of the research is the spleen of male layer chickens. Isolation of Salmonella sp performed by inoculating spleen that were pierced using a swab on the media Selenite Cystine Broth (SCB) then planted on selective media Salmonella Shigella Agar (SSA) and colony morphology was observed, continued with observation of Gram stain under microscopic. Furthermore, colonies of suspected Salmonella sp planted in the media MR-VP (Oxoid), Indol (Difco), Simmons's Citrate Agar (Oxoid), Triple Sugar Iron Agar (TSIA), Sulfite Indol Motiliti (SIM), and media sugars (sucrose, manitol, glucose, lactose , maltose). The results of this study were analyzed descriptively. The research shows a results from a total of 33 samples, we found that 15 samples are positive that can be isolated and identified as Salmonella sp. Therefore it can be concluded that Salmonella sp is possible the death cause of male layer chicken in farms Sibreh, Aceh Besar